Anthropometric Changes in the Upper Lip Between the Standing Position in the Clinic and Supine Position on the Operative Table in Secondary Cleft Lip Nasal Deformities. Issue 5 (May 2021) - Han, Kihwan; Kim, Taeki; Kim, Junhyung; Choi, Jaehoon; Shin, Youngmin; Jeong, Woonhyeok
Abstract : Background: We evaluated changes in lip height and length by position in cleft lip nasal deformity patients who underwent treatment with Millard technique. Methods: A retrospective review of the medical records and an anthropometric analysis of photographs were performed in 209 cases of cleft lip nasal deformity. In the photogrammetric analysis, the lip height and length were calculated with respect to the intercanthal width. To evaluate the change in the difference between the cleft- and noncleft-side measurements between the standing and supine positions, the difference between the cleft- and noncleft-side measurements (Δ nc-c) was calculated. We identified which patients and surgical factors affected the difference between the cleft- and noncleft-side measurements between the standing and supine positions (Δ st-sp). Results: From a total of 120 cases, cases with missing medical charts and clinical photographs were excluded, and 89 cases were included in this study. The discrepancy between the cleft-side lip height and noncleft-side lip height was significantly different between the standing and supine positions ( P = 0.007). According to the univariate regression analysis, Δ st-sp (sbal-cphi) had a significant positive correlation with body mass index ( P = 0.044). In the final multiple linear regression analysis, body mass index had a significant positive correlation with Δ st-sp (sbal-cphi, P = 0.044 ). Conclusion: In our results, the difference in vertical lip height is easy to underestimate in the supine position during surgery. Therefore, surgeons should verify lip height with the patient in the sitting or standing position during the operation to avoid undercorrecting lips with short heights.